2. (3,1) and (3,-1)
5x + 8y = –29
7x – 2y = –67
To complete the square for the equation X^2 + 16X + __ = 18 + __, we need to add 64 to both sides to get the equation X^2 + 16X + 64 = 18 + 64.
To complete the square for the given quadratic equation, we need to add a specific value to both sides of the equation. That specific value is the square of half the coefficient of the X term. In this case, the X term's coefficient is 16, so we need to take half of 16 (which is 8) and square it (which is 64).
So, the number to be added to both sides of the equation is 64.
The completed square equation then becomes: X^2 + 16X + 64 = 18 + 64.
Learn more about Completing the square here:
#SPJ2
The probable question may be:
What number needs to be added to both sides of the equation in order to complete the square?
X^2+16X+____=18+___
Answer:
16
Step-by-step explanation:
Given x^2 + 16x = 18. Complete the square:
Take half of the coefficient of x (in other words, take half of 16) and square the result: we get 8^2 = 64.
Add 64, and then subtract 64 from x^2 + 16x + 64 = 18 + 64
Then (x + 8)^2 = 82. From this point on it's easy to find the roots, but we were not asked to do so.
The desired number is 64; note that it is (16/2)^2.
Answer:
Hi! The correct answer is 7x=-3!
Step-by-step explanation:
~Write in standard form~
The equation 7x+y+3=y is a linear equation as it consists of variables to the first degree, but it's not in the standard form. Upon rearranging, the standard form will be 7x - 3 = 0.
Yes, the equation 7x+y+3=y is a linear equation because it represents a straight line when plotted on a graph. This is because it consists only of the first degree variables (that is, variables raised to the power of 1) of x and y, which define linear equations. However, it is not in the standard form. The standard form of a linear equation is usually written as Ax + By = C, where A, B, and C are constants and x and y are variables, and A and B are not both zero. Therefore, to express this equation in standard form, we need to rewrite it, resulting in the equation 7x + y - y - 3 = 0 or 7x - 3 = 0.
#SPJ3